Social Media and the Interpretation of Islamic Inheritance Law: Insights from Muhammad Abu Rivai’s Instagram - Muhammad Abu Rivai; Deri Eka Putra; Abdurrahman Siregar; Muh Rizki; Jusniati Sari (Fiat Justisia: Jurnal Ilmu Hukum, 2025)
In the digital era, social media has become a key medium for disseminating Islamic legal knowledge. This study analyzes the Instagram account of Muhammad Abu Rivai, which promotes Islamic inheritance law through accessible content. Using a qualitative-descriptive method and content analysis of 30 posts from January 2023 to January 2024, the research examines engagement metrics and content relevance to core inheritance issues. Applying the maqāṣid al-sharīʿa framework, the study finds that the account effectively simplifies complex legal concepts, enhancing public understanding of inheritance law and supporting the preservation of lineage (ḥifẓ al-nasl), property (ḥifẓ al-māl), and religion (ḥifẓ al-dīn). However, limited depth and interactivity in some posts pose risks of misinterpretation. The study recommends greater scholarly collaboration and interactive features to improve the accuracy and educational value of Islamic legal content on social media.